Green synthesis of Opuntia-derived carbon nanodots for the catalytic decolourization of cationic dyes. (5th November 2020) - Beker, Sabrina A.; Truskewycz, Adam; Cole, Ivan; Ball, Andrew S.
Abstract : Carbon nanodots, rich in functional groups and synthesised using green precursors, catalyse the decolourization of dyes under mild conditions. Abstract : The continued discharge of synthetic dyes into aqueous ecosystems from industrial effluent sources represents a critical issue for both human and environmental health. Although there exist various treatments for the treatment of dye-containing wastewater, a low-cost, green, effective, and ecofriendly approach still remains to be developed. In this work, carbon nanodots were synthesised using prickly pear and urea as green precursors and tested as catalysts in the Fenton-like reaction for the catalytic decolourization of cationic dyes. Approximately 90% of a mix of three common cationic dyes (crystal violet, basic fuchsin and methyl green) at 5 × 10 −5 M were removed from water at 20 °C and pH 7.5 in the presence of H2 O2 at 0.5% after only 60 minutes. The carbon nanodots utilised in this study were characterized by FTIR, XPS, zeta potential, UV-Vis and TEM. They exhibited negative surface charge, excellent aqueous solubility, and nitrogen rich surface functionalities which were involved in the transference of electrons, participating in the decomposition of H2 O2, and therefore generated hydroxyls, superoxide ions and singlet oxygens as detected using the free radical quenching technique. This work provides an insight into exploiting an ecofriendly non-toxic metal-free catalyst using a low cost and efficient approach that showed promising decolourization results, without the use of external energy, at a neutral pH solution that could be potentially applied in catalysis of a range of environmental pollutants.